COMBINED STRATEGY IN AAA ELECTIVE TREATMENT - Utikal, Petr; Kocher, Martin; Koutna, Jirina; Bachleda, Petr; Drac, Petr; Cerna, Marie; Buriankova, Eva; Herman, Jiri (Biomedical papers, 2005)
The authors describe surgical treatment for high risk patients with abdominal aortic aneurysms of complicated morphology for standard endovascular repair. This was achieved by combining endovascular stent-grafting for aneurysmal sac exclusion with conventional vascular surgical procedures.
Keywords: Aorta/Aneurysms/Repair/Strategy/Surgery/Endovascular/Combined